The Influence of Educational Technology, Social Interaction and Learning Style on Learning Outcomes with Learning Interest as An Intervening Variable in Class X Students in Madrasah Aliyah Negeri 1 Makassar City - Nurjannah, Nurjannah; Rijal, Syamsu; Riskawati.B, Riskawati.B; Mustari, Mustari (Eastasouth Institute, 2024)
This research aims to gain knowledge and understanding regarding the influence of educational technology, social interaction and learning styles on learning outcomes with interest in learning as an intervening variable in class X students at Madrasah Aliyah Negeri 1 Makassar City. The method used is quantitative research techniques with descriptive research type. The sample in this study was 113 class X students. Data analysis used the Partial Least Square Structural Equation Model (PLS-SEM). The research results obtained were that Educational Technology, Social Interaction and Learning Style had a significant effect on the Learning Outcomes of class X students. Interest in Learning was able to mediate Educational Technology on Learning Outcomes. Interest in Learning is able to mediate Social Interaction on Learning Outcomes. Learning Interest is able to mediate Learning Style on Learning Outcomes.